2022
DOI: 10.2217/cer-2022-0160
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare and economic burden of anticholinergic use in adults with overactive bladder: a systematic literature review

Abstract: Aim: To determine the economic burden associated with anticholinergic medication use in adults with overactive bladder (OAB) in the USA. Methods: A systematic literature review was conducted to identify articles assessing healthcare resource utilization (HCRU) and costs associated with anticholinergic use in adults with OAB. Results: From the 34 articles identified, increased anticholinergic burden, switching anticholinergic treatments and potentially inappropriate anticholinergic use were associated with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…According to studies, the prevalence of OAB in women aged 18 years and above varies widely, ranging from approximately 17% to 43% in Europe and the United States [2][3][4][5][6] to approximately 1.9% to 53.8% in Asia [7][8][9][10][11]. Relevant reports have also demonstrated that OAB affects patients' quality of life (QOL) and incurs high medical costs [12]. There may be many OAB patients in China's enormous population, and reliable estimates of OAB prevalence are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…According to studies, the prevalence of OAB in women aged 18 years and above varies widely, ranging from approximately 17% to 43% in Europe and the United States [2][3][4][5][6] to approximately 1.9% to 53.8% in Asia [7][8][9][10][11]. Relevant reports have also demonstrated that OAB affects patients' quality of life (QOL) and incurs high medical costs [12]. There may be many OAB patients in China's enormous population, and reliable estimates of OAB prevalence are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review found that increasing anticholinergic use or burden, low persistence, and potentially inappropriate anticholinergic use (as defined by Beers Criteria) were all associated with increased health care utilization and costs to the payer. 9 In addition, a cost-effectiveness model that considered anticholinergic-related adverse events found that a b 3 -adrenergic receptor agonist can be cost-effective compared with anticholinergics from a commercial and Medicare payer perspective. 10 Health plans should reevaluate, and consider abandoning, requirements to trial anticholinergic treatments before other treatment options for overactive bladder.…”
mentioning
confidence: 99%